POLITIK HUKUM PENGATURAN HAK ASAL USUL DESA ADAT DALAM UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Abdul Adib Raimudin; Gusliana HB; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
In the government system of the Unitary State of the Republic of Indonesia,villages have authority based on origin rights as regulated in Village LawNumber 6 of 2014 article 19 letter a as emphasized in the explanation, namelyrights which are living inheritance and village initiatives or village communityinitiatives in accordance with with the development of society. In addition, basedon Law Number 6 of 2014 concerning Villages, Villages are interpreted asVillages and Traditional Villages or what are called by other names, are legalcommunity units that have territorial boundaries that are authorized to regulateand manage Government Affairs, the interests of the local community based oncommunity initiatives, rights of origin, and/or traditional rights that arerecognized and respected in the government system of the Unitary State of theRepublic of Indonesia. The Village Law recognizes the autonomy possessed by theVillage. Village autonomy is defined as providing opportunities to grow anddevelop following the development of the community itself. Villages, or other verydiverse names in Indonesia, were originally local community organizations thathad territorial boundaries, were inhabited by a number of residents, and hadcustoms to manage themselves, called self-governing communities.The type of legal research used is normative legal research, normative legalresearch is research conducted to collect and analyze secondary data. Innormative legal research, secondary data sources are usually only used, namelybooks, diaries, statutory regulations, court decisions, legal theories and opinionsof leading legal scholars.Efforts must be made so that obstacles in the implementation of the formation ofTraditional Villages can be realized to the fullest, namely: (a) Accelerating theformation of Provincial Regulations and their implementing regulations related toTraditional Villages, (b) Providing Comprehensive Traditional Village Referencesand Studies, (c) Increasing Knowledge of Government Apparatus and Communitytowards Traditional Villages, and (d) Optimizing the socialization of RegionalRegulations related to Traditional VillagesKeywords: Origin Right - Traditional Village - Government.